Global justice and disasters. Issue 2 (24th January 2013) - Clark, Nigel; Chhotray, Vasudha; Few, Roger
<x xml:space="preserve">Abstract</x> Critical inquiry into the relationship between natural hazards and disasters has raised pressing questions about the uneven exposure and resilience of different social groups. This paper argues that human‐induced climate change and its implication in a range of extreme events extends and complicates the pursuit of justice in the context of differentiated vulnerability to hazards. But the challenge of living with natural hazards can provoke and inspire the idea of global environmental justice in other ways. Sustained consideration of the unpredictability of physical environments draws us into engagement with the temporality and spatiality of earth processes. It points to the ways that any extended place‐based inhabitation must involve demanding accommodations to environmental uncertainty – raising questions about how to 'do justice' to these achievements. Confronting forms of hardship that are triggered by the dynamics of the earth itself can also be taken as a prompt to conceive of environmental justice not only in regard to what others deserve or are entitled to, but in terms of what might be offered simply in response to their suffering. In this way, the paper proposes, thinking through natural hazard and disaster might play a part in re‐imagining the very concept of environmental justice.